Dari genealogi menuju keberlanjutan: Mbah Yahuda dan relasi ideologis pesantren Mataraman - Muhammad Muntahibun Nafis; Rizqa Ahmadi; Azmil Tayeb (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
The development of Islam in the Indonesian archipelago is closely tied to the networks of scholars, including those in the Mataraman region, where Mbah Yahuda played a pivotal role in transmitting Islamic knowledge in the southern area of Java. This study contends that Mbah Yahuda significantly contributed to the spread of Islam through pesantren, which served as centers of classical Islamic scholarship. His long-standing influence is seen in the establishment of major pesantren such as Lirboyo, Ploso, and Jampes in Kediri, as well as others in Trenggalek, Ponorogo, and Pacitan. These institutions share genealogical and intellectual connections that can be traced back to him. Preliminary genealogical data reveals three theories regarding Mbah Yahuda’s origins: a Middle Eastern lineage linked to Sayyidina Hamzah, evidenced by the historical gifting of the KamKam Sword; a Cirebon connection suggested by the presence of a nagasari tree near his tomb; and a Mataram royal lineage supported by genealogical records. His descendants, particularly the Egyptian clan, are associated with pesantren traditions focused on Qur’anic studies and Sufism, while others are known as scholars and government officials. Overall, the scholarly networks rooted in Mbah Yahuda underline the strategic contribution of Indonesian Islamic traditions to sustainable development goals, especially in quality education, peacebuilding, and cultural preservation.